Pre-harvest treatment with gibberellin (GA3) and nitric oxide donor (SNP) enhances post-harvest firmness of grape berries - Lingling Hu; Qianqian Zheng; Zhihui Chen; Yi Qin; Haoxuan Si; Jiayi Ji; Qing Li; Zhongyi Yang; Yueyan Wu (Food Chemistry: Molecular Sciences)
Grapes are prone to softening, which limits their shelf life and suitability for long-distance transport. This study explored the molecular mechanisms underlying the effects of the chemical preservatives gibberellin (GA3) and the nitric oxide donor sodium nitroprusside (SNP) on grape firmness. Enhancing grape quality, prolonging shelf life, and extending market supply were key objectives. Using transcriptomic and physicochemical analyses, the study found that treatments with 3 mmol/L GA3 and 20 μmol/L SNP significantly increased the firmness of ‘Yinhong’ grapes, thereby improving overall quality. The mechanisms of action, however, differed between the two treatments. GA3 inhibited pectin degradation and promoted cellulose accumulation, whereas SNP enhanced lignin and cellulose accumulation, by modulating cell wall metabolism. Furthermore, transcription factors such as CYPs, NAC043, and WRKY33 were identified as key regulators working in concert with target genes to influence berry firmness. These findings highlight the critical roles of GA3 and SNP in improving grape quality and extending storage potential.